Penerapan Risha Model Edukasi Kipi Berbasis Android pada Ibu yang Memiliki Anak Usia 1-24 Bulan - Yuniarni, Riyana Risha; Santoso, Bedjo; Wahyuni, Sri (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the Android-based educational model for handling post-immunization adverse events (AEFI) on behavior in dealing with AEFI in mothers who have children aged 1-24 months. The method used is Research and Development (R&D) and the Quasy Experimental Control Group Pre-test and Post-test Design study model test. The research subjects were 36 mothers with children aged 1-24 months and were divided into two groups. Risha, an Android-based AEFI handling education model, gave the treatment for one week with three meetings. The control group will receive education using leaflets for one week with three sessions—dependent variables: knowledge, attitudes, and skills. The data collection process uses a knowledge, attitudes, and skills questionnaire regarding handling AEFI. The model data was tested using the Mann-Whitney and Wilcoxone difference tests. The research results show that Risha's Android-based educational model for managing AEFI is effective in increasing knowledge (0.000), attitudes (0.000), and skills (0.011) of mothers who have children 1-24 months. This research concludes that Risha's Android-based educational model for handling AEFI is suitable for use to improve maternal behavior in dealing with AEFI in children aged 1-24 months. Keywords: Android, Skills, AEFI, Knowledge, Attitude